APLIKASI KARBON AKTIF DARI CANGKANG KELAPA SAWIT DENGAN AKTIVATOR H3PO4 UNTUK PENYERAPAN LOGAM BERAT Cd DAN Pb - Erika Mulyana Gultom, M. Turmuzi Lubis (Universitas Sumatera Utara, 2014)
This research aims to determine the optimum conditions ofactivated carbon made of palm shells activated with H3PO4as an absorber of heavy metals such as Cd and Pb. The research methodology includes the preparation of activated carbon, absorption, and testing. Absorption stage is done by varying the concentration of heavy metals are 5 ppm, 10 ppm, 15 ppm, 20 ppm and activated carbon mass per run, which is0.5 grams. Another variable are the contact time with intervals of 5 minutes and the pH arranged heavy metals 2-9. Testing activated carbon absorption to heavy metals using atomic adsorption spectrofotometric (AAS). The results showed that the most optimum absorption is concentration of 10 ppm, 40 minutes and pH absorption3-4. Absorption of heavy metals Cd and Pb obtained 84,61 % and 80,13 %.